Evaluating the effectiveness of Leadership Development in Healthcare - Bunting, Lyndsay C (2017)
Organisations across both public and commercial sectors consider leadership to be important but the evidence for a link to organisational performance is complicated. Nonetheless, much of the literature on leadership development indicates that the hallmarks of successful leadership development programmes are those that are clearly and transparently linked to strategic organisational aims and objectives.